Performance analysis of industrial robots in handling hard disk drive - Mohd Sa'at, Zaid (2014)
Data storage device such as hard disk drive (HDD) has evolved tremendously in the market today. The demanding capacity output from the biggest player of this core business mainly comes from the Western Digital Malaysia Sdn Bhd.(WDM). WDM production continues to improve it utilizations from the investment on the several types of industrial robots with diverse capabilities, facilities and specification. Identically, three types of robot are critically used. They are selective compliance assembly robots ann (SCARA), Cartesian coordinates robot and articulated robot. In order to meet the world class manufacturing standards, the performance analysis of these robots has become an important criterion to be considered. This paper presents the application of an overall equipment efficiency (OEE) as a method to compare all the three types of robots performance analysis. Systems reporting through the automation logs are being revised to suit the OEE requirement. The data collection for the system reporting are developed using the software dispatcher and system database. The analysis tools for the result is expressed using the Microsoft excel. Based on overall selected criterion, the obtained result shows that the six joint articulated robot is ranked as the robot with the best performance. Second place goes to SCARA and the lowest is Cartesian coordinates robot.